Kredit Usaha Rakyat (KUR): Jalan Pintas Atau Solusi untuk Kemiskinan Multidimensi di Indonesia? - Harsya Saputra; Hefrizal Handra; Sri Maryati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the impact of the People’s Business Credit Program (KUR) on reducing multidimensional poverty in Indonesia. Using the Propensity Score Matching (PSM) method, this research measures the effectiveness of KUR in improving community welfare by expanding access to financing. The findings indicate that KUR has a significant impact on reducing multidimensional poverty, primarily through increased access to business capital, job creation, and higher household income for beneficiaries. These results align with previous studies highlighting the role of microcredit in poverty alleviation. However, the effectiveness of KUR depends on policy implementation and local conditions. Therefore, integrating KUR with other empowerment programs, such as entrepreneurship training and financial literacy, is necessary to maximize its impact. Additionally, the government is encouraged to strengthen monitoring and evaluation systems to ensure the program's long-term sustainability. Through these measures, KUR is expected to become more effective in enhancing community welfare and reducing socio-economic disparities in Indonesia.